Issues & Challenges Faced While Using Digital Payment Method: Survey of ATM/Debit Card Users (Trinity Journal of Management, IT & Media (TJMITM), 2021)
Today use of ATM/Debit Card even in developing countries has become a  common scenario. People use it to shop, pay bills and for online transactions etc.  But with increase in number of Debit Card users, the various issues & challenges  have also been on rise. The objective of the proposed paper is to study the extent  of various issues & challenges faced by ATM/Debit card users while using various  services provided by different banks operating in four administrative division of  Haryana (Gurgaon, Rohtak, Hisar & Ambala) and Delhi. To achieve the objective  of the study primary data was collected through a structured questionnaire from  the respondents using ATM/Debit card Services (public, private and foreign  banks). In total 750 respondents were studied by using a convenience sampling  method. To analyze the collected data SPSS version 19 was used. The various  statistical techniques i.e. frequency distribution, percentages, mean, and standard  deviation were used for analysis. To test the null hypothesis parametric test such  as t-test and ANOVA were used. The major findings of the study reflected that  “Fast cash withdrawals”, “View account balance and mini statements”, “Pay your  utility bills” and “Railway/air ticket/other ticket bookings” are major transactions  frequently used by the ATM/Debit card users, while users frequently faced issues/ problems i.e. “Machine out of order”, “Maximum cash withdrawal is limit fixed”,  “Machine out of cash” and ‘Debit cards get blocked’ up to a large extent. Further  demographic variables showed significant relation with various issues & challenges  faced by ATM/Debit card users. The study provides meaningful direction to bank  management and decision maker to minimize the frequency of occurrence of the  various problems/issues & challenges while using ATM/Debit card services for  higher customer satisfaction.
Keywords: ATM; Online; Issues; Challenges